The alpha-2A adrenoceptor agonist guanfacine improves sustained attention and reduces overactivity and impulsiveness in an animal model of Attention-Deficit/Hyperactivity Disorder (ADHD) - Sagvolden Terje (Behavioral and Brain Functions, 2006)
Abstract Background ADHD is currently defined as a cognitive/behavioral developmental disorder where all clinical criteria are behavioral. Overactivity, impulsiveness, and inattentiveness are presently regarded as the main clinical symptoms. There is no biological marker, but there is considerable evidence to suggest that ADHD behavior is associated with poor dopaminergic and noradrenergic modulation of neuronal circuits that involve the frontal lobes. The best validated animal model of ADHD, the Spontaneously Hypertensive Rat (SHR), shows pronounced overactivity, impulsiveness, and deficient sustained attention. While dopamine release is decreased in SHR prefrontal cortex, norepinephrine concentrations are elevated. The noradrenergic system appears to be hyperactive as a result of impaired alpha-2A adrenoceptor regulation. Thus, the present study tested behavioral effects of the centrally acting alpha-2A adrenoceptor agonist guanfacine on SHR behavior. Methods The present study tested behavioral effects of guanfacine at doses of 0.075, 0.15, 0.30 and 0.60 mg base/kg i.p. in both male SHRs and their controls, the Wistar Kyoto rat (WKY). ADHD-like behavior was tested with a visual discrimination task measuring overactivity, impulsiveness and inattentiveness. Results The striking impulsiveness, overactivity, and reduced sustained attention during baseline conditions in the SHR improved by treatment with guanfacine. The most pronounced improvement in SHR behavior was seen following the two highest doses (0.3 and 0.6 mg/kg) of guanfacine when SHR behaviors virtually normalized. The positive effects of the drug were most marked towards the end of the session. Conclusion The results indicate that guanfacine improved poor noradrenergic modulation of neuronal circuits that involve the frontal lobes in an animal model of ADHD. The present results support the beneficial effects of guanfacine on ADHD behavior reported clinically and experimentally in primate models of frontal function. It is likely that guanfacine improved prefrontal functions in the SHR. It cannot be concluded, however, that the effects of the drug are mediated solely by norepinephrine.